Easter surprise - Berenstain, Stan & Jan (New York Scholastic, 1998)
As the Berenstain Bears prepare to celebrate Easter, Papa, Mama, and Brother reminisce about another Easter when Brother was given a very special surprise.
02/2006, unk
Keywords: Babies -- Fiction; Easter -- Fiction; Brothers and sisters -- Fiction; Bears -- Fiction